Moldova - Agricultural Policy Notes : Policy Priorities for Agricultural Development, Volume 2. Public Expenditures - World Bank (Washington, DC, 2014)
The objective of this policy note on land is to assist the Government of Moldova in improving the effectiveness of land management in agriculture, with a view to enhancing the sector's contribution to Moldova's economic growth and poverty reduction objectives. The note reviews the progress that has been made to date on land reform in Moldova, and provides rigorous economic analysis of the impacts of the reforms and the state of land markets today. It also makes recommendations on options for improving the functioning of land markets. This note is organized as follows. Chapter one explore in detail the progress of land reform, including changes in land ownership and land use since 1990; then describe the results of farm reorganization efforts, including some comparisons with farm structure in market economies. Chapter two examines the impacts of land reform on economic indicators such as productivity for different farm types. Chapter three analyze the development of land markets to date based on new information gathered for this work from the Cadastre Agency, a survey of farms carried out for this study, and other sources. Finally, chapter four provide recommendations based on international best practice for increasing the efficiency of land use by improving the functioning of land markets, including practical advice for implementing pilot land re-parceling projects.